TECHNICAL EDUCATION AS A PANACEA FOR CURBING BANDITRY AND SECURITY CHALLENGES IN NORTHWEST NIGERIA - CALEB BEM APINEAN; BENJAMIN K.K ANGO (International Studies Journal)
Banditry is among the major security trepidations stifling development in the Northwest and Nigeria at large. This has heighted insecurity and internal displacements in the region with humanitarian issues as farmers have limited access to their farms. Despite government’s attempts to end insecurity in the region it has been proven abortive. This paper therefore examined leadership challenge in inculcating technical education in the context of unending banditry in Northwest Nigeria. Relying on secondary sources, the paper drew extensively from the state fragility theory and posited that the lackadaisical attitudes of Nigerian government to introduce technical and vocational education has caused a lot of challenges to the ever-growing population that relies on farming and pastoralism for survival. The paper submitted that governments of the Northwest Nigeria have not invested in technical education which has made the youth vulnerable to banditry. The paper concluded that until the government invest in formal education that is technically inclined to get the youth engaged, banditry will continue to be the order of the day. To do this government has to direct the budgetary allocation to education with sincerity of releasing the budgeted funds for the implementation of technical oriented educational programmes for the youths. Also, the stake holders have to engage the youth in meaningful projects to make them self-sustaining.   This can start with abolishing the Almajiri system in the region so that parents will be held responsible for the upbringing of their children.